MODELLING OF THE ARNEODO CHAOTIC SYSTEM USING LABVIEW - Rusyn , Volodymyr; Paraduha , Artur; Bakum , Dmytro; Makarov , Egor; Homitskii , Anton (Collection of scientific papers «ΛΌГOΣ», 2024)
A chaotic system refers to a dynamic system that appears to be random and unpredictable, even though it is governed by deterministic laws. In simpler terms, chaotic systems are sensitive to initial conditions, meaning small differences in the starting state of the system can lead to vastly different outcomes. This phenomenon is often called the butterfly effect, where small changes can have large, unpredictable consequences over time.